The Interplay Between Prenatal Adversity, Offspring Dopaminergic Genes, and Early Parenting on Toddler Attentional Function - Szekely, Eszter; Jolicoeur-Martineau, Alexia; Atkinson, Leslie; Levitan, Robert D.; Steiner, Meir; Lydon, John E.; Fleming, Alison S.; Kennedy, James L.; Wazana, Ashley (Frontiers in Behavioral Neuroscience, 2021)
Background: Few studies have explored the complex gene-by-prenatal environment-by-early postnatal environment interactions that underlie the development of attentional competence. Here, we examined if variation in dopamine-related genes interact with prenatal adversity to influence toddler attentional competence and whether this influence is buffered by early positive maternal behavior. Methods: From the Maternal Adversity, Vulnerability and Neurodevelopment cohort, 134 participants (197 when imputing missing data) had information on prenatal adversity (prenatal stressful life events, prenatal maternal depressive symptoms, and birthweight), five dopamine-related genes (DAT1, DRD4, DRD2, COMT, BDNF), observed maternal parenting behavior at 6 months and parent-rated toddler attentional competence at 18 and 24 months. The Latent Environmental and Genetic InTeraction approach was used to examine genes-by-prenatal environment-by-postnatal environment interactions while controlling for sociodemographic factors and postnatal depression. Results: Our hypothesis of a three-way interaction between prenatal adversity, dopamine-related genes and early maternal parenting behavior was not confirmed. However, consistent two-way interactions emerged between prenatal adversity and dopamine-related genes; prenatal adversity and maternal parenting behavior, and dopamine-related genes and maternal parenting behavior in relation to toddler attentional competence. Significant interaction effects were driven by the DAT1, COMT, and BDNF genotypes; prenatal stressful life events; maternal sensitivity, tactile stimulation, vocalization, and infant-related activities. Conclusions: Multiple dopamine-related genes affected toddler attentional competence and they did so in interaction with prenatal adversity and the early rearing environment, separately. Effects were already visible in young children. Several aspects of early maternal parenting have been identified as potential targets for intervention.